A multi-defense strategy: Enhancing bactericidal activity of a medical grade polymer with a nitric oxide donor and surface-immobilized quaternary ammonium compound. (August 2017) - Pant, Jitendra; Gao, Jing; Goudie, Marcus J.; Hopkins, Sean P.; Locklin, Jason; Handa, Hitesh
Graphical abstract: Abstract: Although the use of biomedical devices in hospital-based care is inevitable, unfortunately, it is also one of the leading causes of the nosocomial infections, and thus demands development of novel antimicrobial materials for medical device fabrication. In the current study, a multi-defense mechanism against Gram-positive and Gram-negative bacteria is demonstrated by combining a nitric oxide (NO) releasing agent with a quaternary ammonium antimicrobial that can be covalently grafted to medical devices. Antibacterial polymeric composites were fabricated by incorporating an NO donor, S -nitroso- N -acetyl-penicillamine (SNAP) in CarboSil® polymer and top coated with surface immobilized benzophenone based quaternary ammonium antimicrobial (BPAM) small molecule. The results suggest that SNAP and BPAM individually have a different degree of toxicity towards Gram-positive and Gram-negative bacteria, while the SNAP-BPAM combination is effective in reducing both types of adhered viable bacteria equally well. SNAP-BPAM combinations reduced the adhered viable Pseudomonas aeruginosa by 99.0% and Staphylococcus aureus by 99.98% as compared to the control CarboSil films. Agar diffusion tests demonstrate that the diffusive nature of NO kills bacteria beyond the direct point of contact which the non-leaching BPAM cannot achieve alone. This is important for potential application in biofilm eradication. The live-dead bacteria staining shows that the SNAP-BPAM combination has more attached dead bacteria (than live) as compared to the controls. The SNAP-BPAM films have increased hydrophilicity and higher NO flux as compared to the SNAP films useful for preventing blood protein and bacterial adhesion. Overall the combination of SNAP and BPAM imparts different attributes to the polymeric composite that can be used in the fabrication of antimicrobial surfaces for various medical device applications. Statement of significance: A significant increase in the biomedical device related infections (BDRIs), inability of the currently existing antimicrobial strategies to combat them and a proportional rise in the associated morbidity demands development of novel antimicrobial surfaces. Some of the major challenges associated with the currently used therapeutics are: antibiotic resistance and cytotoxicity. In the current study, engineered polymeric composites with multi-defense mechanism were fabricated to kill bacteria via both active and passive mode. This was done by incorporating a nitric oxide (NO) donor S -nitroso- N -acetypenicillamine (SNAP) in a medical grade polymer (CarboSil®) and a benzophenone based quaternary ammonium antimicrobial small molecule (BPAM) was surface immobilized as the top layer. The developed biomaterial was tested with Gram-positive and Gram-negative strains and was found to be effective against both the strains resulting in up to 99.98% reduction in viable bacterial count. This preventative strategy can be used to fabricate implantable biomedical devices (such as catheters, stents, extracorporeal circuits) to not only significantly limit biofilm formation but also to reduce the antibiotic dose which are usually given post infections.